Fabrication of a reversible SnS2/RGO nanocomposite for high performance lithium storage. Issue 38 (31st March 2016) - Yan, Shancheng; Li, Keyu; Lin, Zixia; Song, Haizeng; Jiang, Tian; Wu, Jiansheng; Shi, Yi
Abstract : Herein, we report a facile solvothermal synthesis of reversible SnS2 /RGO nanocomposites with improved reversibility in Li + storage. Abstract : SnS2 /graphene (SnS2 /G) composites have been explored extensively as a promising candidate for Lithium Ion Battery (LIB) anodes in recent years. Previously, the SnS2 conversion/reduction step of the reaction mechanism is generally believed to be irreversible or only partially reversible, which severely underestimates the theoretical capacity of SnS2 . In this work, SnS2 nanoparticles have been successfully stacked on reduced graphene oxide (RGO) via a facile and effective solvothermal method using ethylene glycol as a chelant. The SnS2 /graphene nanocomposite retained many of the original 2D characteristics of the graphene nanosheets. As a result, Li + storage properties were significantly improved. The SnS2 /RGO nanocomposites show a higher storage capacity of 939.0 mA h g −1 after 30 cycles at a current density of 0.1 A g −1, and a long-term cycle capacity of 615.5 mA h g −1 even after 200 cycles at 1 A g −1 . The superior cycling stability of the SnS2 /RGO electrode is attributed to greater reversibility in the initial conversion reaction, ascribed to the presence of the Sn nanoparticles.